(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
National values and spirituality are among the key pillars of social progress. This study aims to analyze the role of national values in ensuring social stability and development, as well as to identify ways to adapt them to modern society. The research process involves a literary analysis and a review of academic sources, examining both historical and contemporary studies to assess the impact of national values on societal advancement. At the same time, globalization and technological progress may lead to the weakening of certain national values. This study explores the role of national values in social development from a philosophical and sociological perspective, proposing strategic approaches to preserving and strengthening them. To reinforce national identity, it is essential to integrate these values into the modernization process. The findings of this study are significant for education, culture, and public policy. In the future, it is crucial to conduct broader sociological research on the influence of national values on society and to examine their transformation processes across different regions based on empirical data. Overall, this paper highlights the role of national values in social development, emphasizing the importance of preserving and adapting them to contemporary realities. Transmitting spiritual heritage to future generations not only contributes to the preservation of national identity but also fosters the establishment of a stable and ethical society.